“Se ele soubesse a minha história”: a narrativa de linguísticas aplicados sobre a experiência do doutorado sanduíche e sua relação com a língua inglesa - Barbato, Cesar Souza (Universidade do Vale do Rio dos Sinos, 2023)
The present research analyzes narratives of applied linguists participating in the Sandwich Doctoral Study Abroad Program (PDSE). It focuses on the role of the English language and its unfoldings in the exchange experience, considering that there is still a gap in the studies of narratives in Applied Linguistics in this field. It also analyzes how the participants perceive the reverberations of the experience abroad in their English teaching practices (error correction, pronunciation, phonetic aspects), as well as verifying the use and value attributed to the language during the exchange experience (difficulties, challenges and transformations that occurred during this period) and understanding the internationalization process in the Brazilian context, since PDSE is one of the initiatives for that, from a critical perspective. The theoretical foundation is based on discussions about globalization (SANTOS, 2021), the internationalization of higher education (KNIGHT, 1994, 2004, 2014), the use of English as a lingua franca (JENKINS, 2009), the geopolitical uses of language (MIGNOLO, 2003; SEIDLHOFER, 2012; VERONELLI, 2015) and decolonial studies (MIGNOLO, 2003; QUIJANO, 2005). The methodology of this research is qualitative, having as analytical theory the narrative approach of Bastos (2008), concepts of positioning (DAVIES and HARRÉ, 1990), narrative performance (BAUMAN, 1986), notions of Discourse (GEE, 2008) and the analysis slides of Biar, Orton and Bastos (2021). Data generation took place through semi-structured and recorded interviews using the Microsoft Teams platform. The data were analyzed according to Biar, Barton, and Orton's (2021) analysis slides approach. The results of the study indicate that the sandwich PhD experience, with regard to language episodes, provides experiences related to accent, pronunciation, prejudice, and language geopolitics. Furthermore, the interviewees who work in the classroom also share how the experience abroad during the sandwich doctorate reverberates in their classroom practices. Studies of this nature contribute to the construction of a decolonized view of the sandwich doctorate, since they problematize aspects related to the idealization of the experience outside Brazil, but also demonstrate the importance of the sandwich doctorate for the construction of the identity and career of the participants/post-graduates/future PhD’s/academics.
Keywords: Doutorado sanduíche; Internacionalização; Geopolítica da língua; Estudos decoloniais; Língua inglesa; Sandwich doctorate; Internationalization; Geopolitics of language; Decolonial studies; English language; ACCNPQ::Lingüística, Letras e Artes::Lingüística